2013
DOI: 10.1007/s12253-013-9638-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Metastasis-Associated in Colon Cancer-1 Associated with Poor Prognosis in Patients with Esophageal Cancer

Abstract: Recent studies have shown that expression of metastasis-associated in colon cancer-1(MACC1) is observed in different types of cancer and plays an important role in tumor metastasis. However, the expression of MACC1 and its possible role in esophageal cancer remains unknown. In this study, we determined the expression of MACC1 in esophageal cancer by utilizing immunohistochemistry and analyzed the relationship between the expression and esophageal cancer prognosis. Immunohistochemistry results showed that 47 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Therefore, MACC1 has been suggested as a potential biomarker for metastasis and invasion of colorectal cancer and primary hepatocellular carcinoma (16). High levels of MACC1 are also associated with lymph node metastasis and TNM stage in esophageal cancer, as well as a lower OS and a higher risk of death (17). The present study demonstrated that positive expression of MACC1 was significantly higher in GTs compared with ATs, and significantly correlated with invasion depth, TNM stage and differentiation status.…”
Section: Macc1 Overexpression Enhances Migration and Invasion In Gastsupporting
confidence: 60%
“…Therefore, MACC1 has been suggested as a potential biomarker for metastasis and invasion of colorectal cancer and primary hepatocellular carcinoma (16). High levels of MACC1 are also associated with lymph node metastasis and TNM stage in esophageal cancer, as well as a lower OS and a higher risk of death (17). The present study demonstrated that positive expression of MACC1 was significantly higher in GTs compared with ATs, and significantly correlated with invasion depth, TNM stage and differentiation status.…”
Section: Macc1 Overexpression Enhances Migration and Invasion In Gastsupporting
confidence: 60%
“…Metastasis-associated in colon cancer-1(MACC1), a newly identified key regulator of hepatocyte growth factor (HGF)-MET signaling, predicts colon cancer metastasis [1-3]. Recently, MACC1 expression has been found in lung cancer [4], hepatocellular carcinoma [5], ovarian carcinoma [6], gastric carcinoma [7], esophageal cancer [8], and nasopharygneal carcinoma [9]. Overexpression of MACC1 associates with the progression of these carcinomas and prognosis of the patients with these carcinomas [4, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…MACC1, first identified as a colon cancer oncogene, potentially functions as an early diagnosis biomarker and is associated with the progression of multiple solid tumors (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Stein et al (12) demonstrated that MACC1 upregulation was associated with benign-malignant tumor transition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have revealed that the abnormal expression of MACC1 may be associated with the development and progression of numerous types of solid tumor, including lung (13,14) and gastric cancer (15)(16)(17)(18), hepatocellular carcinoma (19)(20)(21), breast cancer (22), glioma (23) and colon (12,24) and esophageal cancer (25). These studies suggested that MACC1 may serve as a key biomarker for recurrence, metastasis and patient survival in multiple types of human cancer.…”
Section: Introductionmentioning
confidence: 94%